Systematic design and stability analysis of a fuzzy logic controller - 이수영; 정명진 (1995)
Although the fuzzy logic controller has been adopted in many engineering applications, its performance is not guaranteed since there is no definite stability analysis. It may be the main factor that we hesitate to adopt the FLC in critical applications. In this paper, a guideline of systematic analysis and design of an FLC is presented for guaranteeing the stability and/or the performance. Based on the well-developed variable structure system theory, we account for the relationship between the tracking accuracy of a control system and the I/O fuzzy set membership shapes of the FLC. It is also possible to explain the performance or the stability of commonly used FLCs through the proposed guideline for the design and analysis. ？ 1995.